The Influence of Intellectual Capital, Shariah Compliance and Islamicity Performance Index on the Financial Performance of Islamic Commercial Banks - Depriska Lailatul Aroof; Iwan Fakhruddin; Ani Kusbandiyah; Ira Hapsari (Jurnal Multidisiplin Madani, 2023)
This study aimed to determine the effect of intellectual capital, sharia compliance, and islamicity performance index on the performance of sharia commercial banks. Sharia compliance is proxied by the zakat performance ratio, the islamicity performance index is proxied by the profit sharing ratio and financial performance is proxied by the return on assets. This study uses a population of commercial banks in Indonesia with a sample of Islamic commercial banks registered with the OJK during the 2017–2021 period. Data processing in this study used the STATA 17 program. The results of this study indicate that the variable intellectual and sharia compliance has a positive effect on financial performance and the islamicity performance index does not affect financial performance